Takotsubo syndrome: translational implications and pathomechanisms - Fan, Xuehui; Yang, Guoqiang; Kowitz, Jacqueline; Akın, Ibrahim; Zhou, Xiao-Bo; El-Battrawy, Ibrahim (International journal of molecular sciences, 2022)
Takotsubo syndrome (TTS) is identified as an acute severe ventricular systolic dysfunction, which is usually characterized by reversible and transient akinesia of walls of the ventricle in the absence of a significant obstructive coronary artery disease (CAD). Patients present with chest pain, ST-segment elevation or ischemia signs on ECG and increased troponin, similar to myocardial infarction. Currently, the known mechanisms associated with the development of TTS include elevated levels of circulating plasma catecholamines and their metabolites, coronary microvascular dysfunction, sympathetic hyperexcitability, inflammation, estrogen deficiency, spasm of the epicardial coronary vessels, genetic predisposition and thyroidal dysfunction. However, the real etiologic link remains unclear and seems to be multifactorial. Currently, the elusive pathogenesis of TTS and the lack of optimal treatment leads to the necessity of the application of experimental models or platforms for studying TTS. Excessive catecholamines can cause weakened ventricular wall motion at the apex and increased basal motion due to the apicobasal adrenoceptor gradient. The use of beta-blockers does not seem to impact the outcome of TTS patients, suggesting that signaling other than the beta-adrenoceptor-associated pathway is also involved and that the pathogenesis may be more complex than it was expected. Herein, we review the pathophysiological mechanisms related to TTS; preclinical TTS models and platforms such as animal models, human-induced pluripotent stem cell-derived cardiomyocyte (hiPSC-CM) models and their usefulness for TTS studies, including exploring and improving the understanding of the pathomechanism of the disease. This might be helpful to provide novel insights on the exact pathophysiological mechanisms and may offer more information for experimental and clinical research on TTS.
Gesehen am 10.08.2023